2021
DOI: 10.1002/dev.22153
|View full text |Cite
|
Sign up to set email alerts
|

Timing‐specific associations between income‐to‐needs ratio and hippocampal and amygdala volumes in middle childhood: A preliminary study

Abstract: It is well known that financial disadvantage is associated with alterations in brain development in regions critical to socioemotional well-being such as the hippocampus and the amygdala. Yet little is known about whether family income at different points in development is differentially associated with these structures. Furthermore, little is known about which environmental factors statistically mediate associations between income and subcortical structure. Using a longitudinal birth cohort and linear mixedef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
3
4
0
Order By: Relevance
“…We found that lower parent occupational prestige increases risk for delayed brain aging in children and adolescents. This finding is consistent with prior evidence linking lower SES to alterations in brain structure (Colich et al, 2020;Hanson et al, 2011;Jednoróg et al, 2012;Luby et al, 2013;Mackey et al, 2015;McDermott et al, 2019;Noble et al, 2015Noble et al, , 2012Ramphal et al, 2021;Ursache et al, 2016) and delays in brain development (Barch et al, 2020;Hair et al, 2015;Hanson et al, 2013). Additionally our finding points to the specificity of parent occupational prestige, above and beyond other household socioeconomic factors on brain age processes, consistent with prior findings showing unique neural correlates of different SES measures (Lawson et al, 2013;Noble et al, 2015Noble et al, , 2012.…”
Section: Parental Occupational Prestigesupporting
confidence: 92%
See 1 more Smart Citation
“…We found that lower parent occupational prestige increases risk for delayed brain aging in children and adolescents. This finding is consistent with prior evidence linking lower SES to alterations in brain structure (Colich et al, 2020;Hanson et al, 2011;Jednoróg et al, 2012;Luby et al, 2013;Mackey et al, 2015;McDermott et al, 2019;Noble et al, 2015Noble et al, , 2012Ramphal et al, 2021;Ursache et al, 2016) and delays in brain development (Barch et al, 2020;Hair et al, 2015;Hanson et al, 2013). Additionally our finding points to the specificity of parent occupational prestige, above and beyond other household socioeconomic factors on brain age processes, consistent with prior findings showing unique neural correlates of different SES measures (Lawson et al, 2013;Noble et al, 2015Noble et al, , 2012.…”
Section: Parental Occupational Prestigesupporting
confidence: 92%
“…Specifically, lower household SES associates with lower total gray matter volume (Dennis et al, 2022; Jednoróg et al, 2012; Luby et al, 2013; Mackey et al, 2015; McDermott et al, 2019), cortical gray matter volume (Luby et al, 2013; Mackey et al, 2015), cortical thickness (Colich et al, 2020; Mackey et al, 2015; McDermott et al, 2019; Noble et al, 2015), and cortical surface area (McDermott et al, 2019) in youth. Regionally, SES is positively associated with hippocampal (Botdorf et al, 2022; Hanson et al, 2011; Jednoróg et al, 2012; Luby et al, 2013; McDermott et al, 2019; Noble et al, 2015, 2012; Ramphal et al, 2021) and amygdala (Assari, 2020; Assari et al, 2020; Luby et al, 2013; McDermott et al, 2019; Ramphal et al, 2021) volumes across childhood and adolescence, although some studies have failed to replicate findings in the amygdala (Hanson et al, 2011; Noble et al, 2012). Lower SES has also been shown to associate with lower global white matter volumes in one study (McDermott et al, 2019) but not in others (Jednoróg et al, 2012; Mackey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been highlighted that in non-clinical samples who have experienced childhood adversity, whole hippocampal volumes are systematically smaller, although findings in whole amygdala volumes are non-convergent ( Calem et al, 2017 ). These studies illustrate the notion that trauma-related stress, irrespective of the effects of mental health disorders, may exert lasting effects on hippocampal and amygdala volumes ( Calem et al, 2017 ; Janiri et al, 2017 ; Nogovitsyn et al, 2020 ; Ramphal et al, 2021 ).…”
Section: Introductionsupporting
confidence: 59%
“…Our measure may reflect the effect of maternal stress on children’s neurodevelopment or may act as a proxy for stress in the home environment, each of which could have separate biological mechanisms; we are limited in our ability to discern this as the cohort study did not include direct report of children’s experience of stress. Our findings are further limited by the measurement of maternal stress at child age 5, as we have recently shown that the effects of poverty on hippocampal volumes in these children were most salient prior to age 4.5 ( 74 ). Timing-specific effects on the hippocampus have additionally been found for general adverse experiences and maternal support ( 24 , 75 , 76 ).…”
Section: Discussionmentioning
confidence: 68%